Geographical Studies of Humor. Issue 10 (October 2014) - Ridanpää, Juha
Abstract Humor is a spatially embedded institution in many ways. Although a highly marginal field of study, the number of geographical studies on humor has been increasing lately. The aim of this article is to introduce the various approaches and also draw connecting links between them. The review shows how practices of popular media are geopolitically charged, how humor is intertwined with issues of social marginalization, how humor operates as an important element in the construction of group cohesion, how humor works as a non‐cognitive element of human actions, feelings, and emotions, as well as how it represents a useful tool for educational and economic purposes, and how all of this has been studied by scholars of geography. The review shows the various directions of the geographical studies of humor at the same time emphasizing that the relevance, variety, and multidimensionality of the topic have not been fully recognized.